HUBUNGAN KEMANDIRIAN DAN KREATIVITAS SISWA TERHADAP HASIL BELAJAR SENI RUPA KELAS IV SD NEGERI 35 PALEMBANG - Meilindya; Treny Hera; Endie Riyoko (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the lack of students’ independence when planning learning activities because they still follow parental directions and the lack of students’ creativity who have not been able to create concepts in making the artwork of collage. Learning outcomes of collage art learning materials with leaves are 41% of students who have not reached the KKM. The research was to determine whether there is a relationship between students' independence and creativity on the fourth-grade students’ art learning outcomes at SD Negeri 35 Palembang. The research used a quantitative correlation method. The sample used was 22 fourth-grade students who were determined by the purposive sampling technique. Data collection techniques used questionnaires, tests, and documentation. Multiple correlation test showed at the level of strong correlation F test with a significant level of 5%, which showed that H0 was rejected and Ha was accepted with a contribution of 56%. The results showed that there was a significant relationship between students' independence and creativity on the fourth-grade students’ art learning outcomes.